From subsistence to simple commodity production: economic relations in two Semai settlements - Nicholas, Colin G. (1985)
This study documents and analyzes the changes occurring in the Semai settlements of Kampung Kuala Tual and Kampung Sungei Buntu since the early 1950s. In particular, the focus is on the transformation of their economies from one which was subsistence-oriented to d ominated by production for exchange. another which was Information and data pertaining to the change in the form of Semai production -- gathered by the participantobservation method -- are analyzed within a theoretical framework which emphasizes the struggle for the effective control of their production.